Is there is any relationship between malocclusion and nutritional pattern of children (Update Dental College Journal, 2015)
Objective: Malnutrition of children results the underdevelopment of skeleton and facial structure, which might causes the malocclusion in developing dentitions. The study was aimed to investigate the relationship between the malocclusion and malnutrition.Method: Cross-sectional observational study was done with structured questioner from 627 school children (276 male, 349 female) of 7 to 15years age. Variable were set according to WHO guideline of malocclusion and malnutrition.Result: Among the study populations subject with malnutrition, having persistent digit sucking habit of more than 6years of age has been associated with malocclusion (OR = 3.1; 95%CI).Conclusion: No association was reported between malnutrition and malocclusion.Update Dent. Coll. j: 2014; 4 (2): 09-13